The Commemoration of the Prophet PBUH’s Mawlid in the Perspective of Islamic Law Thought of Abu Umar Basyier and Al-Hamid Al-Husaini - Linda Novianti; Ayi Yunus Rusyana; Iman Hilman Faturachman (Journal of Islamicate Studies, 2022)
Of the many polemics that have grown among Muslims, the concept of the law on the commemoration of the Prophet's birthday has become a separate issue that has given rise to pros and cons among the public. In the opinion of Abu Umar Basyier who categorizes that the law commemorating the Prophet's birthday is bid'ah dhalalah whose legal status is illegitimate, while according to H.M.H Al-Hamid Al-Husaini it is categorized as bid'ah hasanah whose legal status is sunnah. The purpose of this study is to find out the arguments used by Abu Umar Basyier and H.M.H Al-Hamid Al-Husaini in establishing the law commemorating the Prophet's Birthday, the legal istinbath method and a comparative analysis between the thoughts of Abu Umar Basyier and H.M.H Al-Hamid Al-Husaini about the commemoration of Maulid Prophet peace be upon him. This research departs from the thoughts of the two figures who are against the concept of bid'ah, so they use the theory of ikhtilaf. Through their respective references, in particular, both of them use a different lens of analysis in applying the meaning of a proposition that becomes a culture in the midst of the life of Muslim society. The method used in this study is the descriptive-analysis-comparative method, namely explaining the legal concept regarding the commemoration of the Prophet's Birthday then comparing and then analyzing based on the data that has been obtained. Based on the discussion that has been presented, it can be obtained the results of the study that Abu Umar Basyier used the bayani method with the argument of al-Qur'an Al-Hasyr verse 7 and Al-Imran verse 31. Meanwhile, Al-Hamid Al-Husaini used the istislahi method with the argument of the Qur'an used, namely the letter Al-Ahzab verse 56 and the letter Hud verse 120. As for the analysis, it can be seen that both of them use the Al-Qur'an and as-Sunnah as the main reference. But what is different, in this case H.M.H Al-Hamid Al-Husaini added maslahah mursalah after the Koran and as-Sunnah.